Asuhan Keperawatan Pada Tn. R Dengan Gangguan Sistem Kardiovaskular: Congestive Heart Failure (CHF) Di Ruang Mawar 1 RSUD dr. Soeselo Kabupaten Tegal - Isma Nur Hidayah; Tati Karyawati (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
Congestive Heart Failure (CHF) is a condition in which the heart is unable to pump blood adequately to meet the metabolic needs of the body. CHF is one of the most prevalent cardiovascular disorders globally, nationally, and locally, contributing to significant morbidity and mortality. This study aims to describe a comprehensive nursing care process applied to a patient (Mr. R) diagnosed with CHF at the Mawar 1 Ward of RSUD dr. Soeselo, Tegal Regency. This study used a descriptive case study design. Data were collected through interviews, physical examination, observation, and medical record documentation on February 9–11, 2026. Three nursing diagnoses were identified: ineffective airway clearance related to airway hypersecretion, fatigue related to physiological conditions (chronic disease), and knowledge deficit related to insufficient information exposure. Nursing interventions applied included airway management (semi-Fowler positioning, oxygen therapy, effective coughing technique), energy management (range-of-motion exercise, gradual activity), and health education about CHF. After 2×24 hours of nursing care, all three nursing diagnoses were resolved: airway clearance improved (SpO₂ increased from 91% to 95%, respiratory rate decreased from 28 to 23 times/minute), fatigue decreased, and patient knowledge about CHF improved. Systematic nursing care significantly improved the patient's condition in CHF management.